Pemanfaatan Podcast sebagai Media Alternatif Pembelajaran Jarak Jauh di SMP Negeri 1 Kajen - Mohammad Syaifuddin; Darmawan Sigit Prastyo (Universitas PGRI Semarang, 2022)
The distance learning during the COVID-19 pandemic has raised various educational problems. However, it raises new creations in utilizing technology to support educational activities. One of them is the use of podcast media as an alternative. This study will discuss how the use of podcast media in the distance learning at SMP N 1 Kajen, Pekalongan district. In conducting the research, the researcher used descriptive qualitative methods with data collection techniques through interviews with the waka curriculum, teachers and students of class VIII, observation and documentation of distance learning activities. The results show that the use of podcast media at SMP N 1 Kajen as an alternative media that is not boring in the distance learning process because it utilizes streaming on the Youtube channel. This media was also responded positively by students with many students providing comments or responses.